VJ Vertov: from the compositing interface to the use of the projection space. (August 2018) - García-Crespo, Oswaldo; Ramahí-García, Diana; Dafonte-Gómez, Alberto
Once digitization had been standardized in the process of audiovisual creation, there has been an improvement over the last decades in the efficiency of storage, coding and transfer systems, an integration of editing and compositing procedures, an increased potential for real-time image and sound manipulation and an increase in the mediation of software and its interface in creative processes. On the basis of both a representative work – Chelovek S Kino-Apparatom ( Man with a Movie Camera, Dziga Vertov, 1929) − and the considerations of Lev Manovich, one of the leading theorists on the subject, this essay is intended as a starting point for addressing issues related to the mutations produced in the traditional concept of film editing as a consequence of the digitization process described above. For this purpose, the authors summarize the results of practical research based on the real-time filmic reinterpretation of the film's editing.